Red Blood Cell Homeostasis and Altered Vesicle Formation in Patients With Paroxysmal Nocturnal Hemoglobinuria - Freitas Leal, Joames K.; Preijers, Frank; Brock, Roland; Adjobo-Hermans, Merel; Bosman, Giel (Frontiers in Physiology, 2019)
A subset of the red blood cells of patients with paroxysmal nocturnal hemoglobinuria (PNH) lacks GPI-anchored proteins. Some of these proteins inhibit complement activation and protect against complement-mediated lysis. This pathology thus provides the possibility to explore the involvement of complement in red blood cell homeostasis, and the role of GPI-anchored proteins in the generation of microvesicles in vivo. Most parameters of red blood cell homeostasis did not show major aberrations of the red blood cell aging process in patients with PNH. Formation of microvesicles, however, which is an integral part of red blood cell homeostasis and aging, is strongly increased in patients with PNH. Also, our data indicate that the absence of GPI-anchored membrane proteins affects the composition of red blood cell-derived as well as platelet-derived vesicles. These data open the way towards a better understanding on the underlying pathophysiological mechanism of PNH, and thereby to the development of new treatment strategies.